2010
DOI: 10.1111/j.1365-2591.2010.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo astaxanthin treatment partially prevents antioxidant alterations in dental pulp from alloxan‐induced diabetic rats

Abstract: Diabetes altered the antioxidant system in dental pulp tissue; astaxanthin partially improved the diabetic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
0
35
0
2
Order By: Relevance
“…The results showed that although having no effect on superoxide dismutase and catalase activities, astaxanthin could stimulate glutathione peroxidase in control and diabetic rats and partially improved the diabetic complications [60]. In addition, Leite et al [68] also evaluated the effect of astaxanthin on the antioxidant enzymes of salivary gland from alloxan-induced diabetic rats, and showed that astaxanthin restored the enzymatic activities in the salivary gland.…”
Section: Dental Pulp and Salivary Glandmentioning
confidence: 96%
See 2 more Smart Citations
“…The results showed that although having no effect on superoxide dismutase and catalase activities, astaxanthin could stimulate glutathione peroxidase in control and diabetic rats and partially improved the diabetic complications [60]. In addition, Leite et al [68] also evaluated the effect of astaxanthin on the antioxidant enzymes of salivary gland from alloxan-induced diabetic rats, and showed that astaxanthin restored the enzymatic activities in the salivary gland.…”
Section: Dental Pulp and Salivary Glandmentioning
confidence: 96%
“…Leite et al [60] evaluated the effect of astaxanthin on antioxidant enzymes of dental pulp from alloxan-induced diabetic rats. The results showed that although having no effect on superoxide dismutase and catalase activities, astaxanthin could stimulate glutathione peroxidase in control and diabetic rats and partially improved the diabetic complications [60].…”
Section: Dental Pulp and Salivary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for its antioxidant capacity, AST is also recognized to have growth performance and survival rate promoting in Atlantic salmon (Salmo salar) (Christiansen and Torrissen 1996) and red porgy (Pagrus pagrus) (Kalinowski et al 2011), skins coloration enhancing in large yellow croaker (Larimichthys croceus) (Yi et al 2014) and Atlantic salmon (Baker et al 2002), anti-lipid peroxidation (Leite et al 2010), and immune response reinforcing in Astronotus ocellatus (Alishahi et al 2015) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Astaxanthin and Antidiabetic Activity: Diabetes mellitus is strongly associated with oxidative stress, which can be a consequence of increased free radical production, reduced antioxidant defenses or both 48 . Oxidative stress induced by hyperglycemia possibly causes the dysfunction of pancreatic b-cells and various forms of tissue damage in patients with diabetes mellitus 49 .…”
Section: Astaxanthin As Powerful Antioxidantmentioning
confidence: 99%